2019
DOI: 10.1371/journal.pone.0220265
|View full text |Cite
|
Sign up to set email alerts
|

The burden of antimicrobial resistance among urinary tract isolates of Escherichia coli in the United States in 2017

Abstract: Urinary tract infections (UTIs) caused by Escherichia coli have been historically managed with oral antibiotics including the cephalosporins, fluoroquinolones and trimethoprim-sulfamethoxazole. The use of these agents is being compromised by the increase in extended spectrum β-lactamase (ESBL)-producing organisms, mostly caused by the emergence and clonal expansion of E. coli multilocus sequence typing (ST) 131. In addition, ESBL isolates show co-resistance to many of oral agents. Management of UTIs caused by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 36 publications
7
75
5
2
Order By: Relevance
“…3b). A high co-occurrence (>30 %) of trimethoprim and ESBL resistance was recently reported in the USA [77]. Furthermore, Mulder et al [78] demonstrated that previous use of extended-spectrum β-lactams in patients with UTIs was significantly associated with trimethoprim resistance.…”
Section: Phenotypic Resistancementioning
confidence: 92%
“…3b). A high co-occurrence (>30 %) of trimethoprim and ESBL resistance was recently reported in the USA [77]. Furthermore, Mulder et al [78] demonstrated that previous use of extended-spectrum β-lactams in patients with UTIs was significantly associated with trimethoprim resistance.…”
Section: Phenotypic Resistancementioning
confidence: 92%
“…Likewise, since none of these BLIs inhibit (18). Of note, none of these agents have oral formulations available for the treatment of infections due to serious or urgent resistant threats in setting where IV therapy is not available or desirable (19).…”
Section: Downloaded Frommentioning
confidence: 99%
“…More serious long-term outcomes include treatment failures, hospitalizations including prolonged stays and readmissions, bacteremia, severe sepsis, septic shock, in-hospital mortality, and the spread of antibiotic resistance. [5][6][7][8][9][10][11][12][13][14][15] For more than 20 years, healthcare providers have prescribed antibiotics with refills for patients with recurrent UTIs so that these individuals can self-treat as symptoms occur, without needing to confirm that bacteria are present in urine. 16 This treatment strategy empowers an individual to begin treatment earlier, so symptoms resolve faster.…”
Section: Introductionmentioning
confidence: 99%